The Non-Observance of Grice Maxims in (The Tv Show) Friends to Create Verbal Humour - Nugroho, Agnesti Pramuktiasih; Faridi, Abdurrahman; Hartono, Rudi (Universitas Negeri Semarang, 2021)
This study focused on the analysis of non-observance Grice conversational maxims utilized by characters in Friends TV Show which involved the flouting maxim, violating maxim, infringing maxim, suspending maxim and opting out maxim. The results of the study showed that that almost all non-observance Grice conversational maxims were utilized in generating verbal humours in which opting out Grice conversational maxim was hardly found to create verbal humour. All types of verbal humours were successfully performed by the characters through flouting conversational maxim in which flouting manner and relation maxims concealed all types of verbal humours due to the irrelevant and ambiguous information delivered by the characters. In addition, the ways the characters being intentionally misleading without any implicature produced had generated humour for the audiences. Furthermore, literalness verbal humour was the most generated humour performed by the characters in infringing the maxims due to characters’ foolishness and lack of imagination. Moreover, suspending Grice conversational maxim was only found in suspended messages and voice call which was funny at the right setting in which there was no implicature produced and expectation to fulfil the maxim. However, there was opting out Grice conversational maxim discovered in this study due to the involvement of third party. For the further study, it is insinuated that the study of verbal humours could be investigated along with the non-verbal communication in order to see the connectivity among the verbal humour and non-verbal communication within conversation.